ANALISIS KEPUTUSAN PEMASARAN TERHADAP KINERJA USAHATANI TANAMAN JAGUNG DI DESA WONUAMBUTEO KECAMATAN LAMBANDIA - Andi Nur Fauzan; La Nalefo; Suriana Suriana (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
The objective of this study is to analyze the marketing decisions that influence the performance of corn farming in Wonuambuteo Village, Lambandia District. The informants in this study are corn farmers residing in Wonuambuteo Village. The informants were selected using purposive sampling, based on criteria established by the researcher. Consequently, the study encompassed 35 corn farmers. The present study employed a qualitative approach. The data were collected through a combination of observation and in-depth interviews. The objective of this study is to examine the factors that influence farming performance, marketing decisions, and the income of corn farmers. The analysis of research data was conducted using qualitative descriptive analysis. The present study employed a qualitative descriptive analysis, which was conducted through three stages: data reduction, data analysis, and data interpretation. Specialized analysis was also conducted using an income formula. The results of the study show that corn farming performance in Wonuambuteo Village has shown positive results thanks to the use of agricultural tools that support efficiency and productivity. Farmers utilize tools such as tractors, high-quality seeds, fertilizers, and harvesting tools that help increase land productivity and reduce working hours. Additionally, marketing decisions have a significant impact on farming performance, with marketing facilities such as traditional and modern markets providing sales channels for corn products. Farmers with land areas of 2.50–3.00 hectares achieve the highest income, ranging from Rp13,000,000 to Rp15,000,000, indicating that increasing land area contributes to improved efficiency and better production outcomes.